Tribute to Lois Ehrenburg at Jon Jon's - Watkins, Howard::::::::: (1981)
Jim Costa speaking at head table with portable microphone system: Margaret Sharp, Karen Humphrey, Dale Doig, Lois Ehrenburg, Mary Nelson seated